Inactivation of the Wnt/β-catenin signaling contributes to the epithelial barrier dysfunction induced by sodium oxalate in canine renal epithelial cells. (21st September 2021) - Ji, Yun; Fang, Shuting; Yang, Ying; Wu, Zhenlong
Abstract: High oxalate consumption has been recognized as a risk factor for renal calcium oxalate stones in companion animals (dogs and cats). However, the cellular signaling involved in oxalate-induced dysfunction in renal tubular epithelial cells remains not fully elucidated. In this study, Mardin–Darby canine kidney (MDCK ) cells, an epithelial cell line derived from canine kidney tubule, were tested for cell proliferation activity and barrier function after being exposed to sodium oxalate (NaOx ). Further, the involvement of Wnt/β-catenin in NaOx-induced renal epithelial barrier dysfunction was evaluated. MDCK cells treated with NaOx exhibited reduction in cell proliferation and migration. Besides, NaOx exposure led to a decrease in transepithelial electrical resistance and an increase in paracellular permeability. The deleterious effects of NaOx on epithelial barrier function were related to the suppressed abundance of tight junction proteins including zonula occludens, occludin, and claudin-1. Of note, protein levels of β-catenin and phosphorylated (p)-β-catenin (Ser552) in MDCK cells were repressed by NaOx, indicating inhibitory effects on Wnt/β-catenin signaling. An inhibition of glycogen synthase kinase-3β (GSK-3β) by SB216763 enhanced the abundance of β-catenin and p-β-catenin (Ser552), and protected against epithelial barrier dysfunction in NaOx-treated MDCK cells. The results revealed a critical role of Wnt/β-catenin signaling in the epithelial barrier function of MDCK cells. Activation of Wnt/β-catenin signaling might be a potential therapeutic target for the treatment of oxalate-linked renal stones.